The Influence of Third-Party Funds, Capital Adequacy Ratio, and Minimum Mandatory Requirements on Mudharabah Financing with Return on Asset as Intervening Variables in Sharia Commercial Banks in Indonesia - Adlina Adlina; Muhammad Ramadhan; Nurlaila Nurlaila (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research aims to examine and analyze the influence of Third-Party Funds (DPK), CAR, GWM and ROA on mudharabah financing at Sharia Commercial Banks in Indonesia. To test and analyze the influence of Third Party Funds (DPK), CAR, GWM on ROA at Sharia Commercial Banks in Indonesia. To test and analyze the influence of Third-Party Funds (DPK), CAR, GWM on mudharabah financing with ROA as an intervening variable at Sharia Commercial Banks in Indonesia. This research approach is a causal associative approach. The research population is Sharia Commercial Bank Companies in Indonesia which are registered with the Financial Services Authority. Observation years start from 2020-2022. Of the 15 existing Sharia Commercial Banks, 8 banks do not present their financial report data every quarter. The data collection method used in this research is a documentation study. Statistical calculation techniques can be carried out using panel data analysis. Analysis of the data obtained is then processed with the help of computer technology, namely Microsoft Excel and also Eviews software. Based on the results of statistical tests and direct discussion, there is an influence of Third-Party Funds, CAR, GWM and ROA on mudharabah financing at Sharia Commercial Banks in Indonesia. There is an influence of Third-Party Funds, CAR, and GWM on ROA at Sharia Commercial Banks in Indonesia. Indirectly, there is an influence of Third-Party Funds, CAR, and GWM on mudharabah financing with ROA as an intervening variable in Sharia Commercial Banks in Indonesia.